Gender differences and climate zones in overweight and obesity prevalence in European elementary school children from 2000 to 2020: a systematic review and meta-analysis - Prvulović, Nikola; Djordjević, Miodrag; Pantelić, Saša (Frontiers in Public Health, 2023)
We face a rapid increase in average global warming of 1.5°C, reported as a syndemic problem of three interconnected epidemics: obesity, global warming, and undernutrition.We aimed to analyze the impact and association between global warming and obesity in children and differences by gender across Europe after 2000.We searched PubMed,MEDLINE,Google Scholar,ScienceDirect, and Embase databases.The considered population were children aged 6-14. Only cross-sectional studies that defined obesity by the IOTF cutoffs and the subjects' place of residence, used to determine precise climate zones, were included. We assessed the prevalence of obesity and overweight using a random-effects and the Mantel-Haenszel fixed-effect method when heterogeneity was greater/lower than 50%.We did a subgroup analysis for prevalence across gender, obesity, and overweight, two decades, regions, countries, and the Köppen-Geiger climate zones.Random effects of the meta-regression were used to study the global warming impact and differences in trends across European countries by gender for both conditions separately.We identified 114 studies that included 985971 children from 39 European countries.A significant difference between genders was in favor of obese girls 4.78 (95%CI:3.85-5.93) versus boys 5.76% (95%CI:5.11-6.48, p=0.03), respectively, but not for overweight children. Most of the obese girls were in South Europe 7.51% (95%CI:6.61-8.51) versus East Europe 2.86% (95%CI:23-3.12), versus boys in South Europe 8.66% (95%CI:7.68-9.74) and North Europe 3.49% (95%CI:2.90-4.19), respectively.The "Cold" Köppen-Geiger climate zone, with lowest temperatures, has the largest trend rise between two decades of 2.8% and 1.53% for obese girls and boys, and 5.31% and 1.81% for overweight girls and boys, respectively, followed by the smallest number of obese girls 3.28% (95%CI:2.17-4.92) and boys 3.58% (95%CI:2.39-5.33), versus the zone with the highest temperatures "Hot" for girls 7.02% (95%CI:6.30-7.82) and for boys 8.23% (95%CI:7.55-8.96), respectively. The meta-regression proved global warming has a significant impact on the distribution of obesity and overweight across climate zones, R2=0.52 and R2=0.22.Our meta-analysis provides a comprehensive overview of the association between and impact of global warming on obesity.This impact increases obesity among children in Europe throughout all climate zones, and emphasizes an urgent call for further preventive methods in schools, since obesity differences continue their trend of disappearing into the future.